Report of DTA pre-inception workshop retreat - Dhulipala, Ram; Muguku, K.; Yassin, L.; Ojanji, Wandera (International Livestock Research Institute, 2025)
The CGIAR Digital Transformation Accelerator (DTA) team convened its inception workshop in Abu Dhabi, United Arab Emirates (UAE), on 18–20 March 2025. This event brought together the DTA core team, CGIAR center representatives and delegates from key CGIAR science programs, including the Gender Equality and Social Inclusion (GESI) Accelerator, Food Frontiers and Security, and Genebanks. Hosted at the Advanced Technology Research Council (ATRC) and AI71, the workshop aimed to build team cohesion, align stakeholder expectations, establish new operational modalities and define next steps for delivering DTA inception goals. Team-building activities and strategy sessions were used to contextualize DTA’s evolving product suite and position within CGIAR’s broader digital innovation agenda. Key thematic sessions focused on the four areas of work (AoW), unpacked through the objectives and key results (OKR) framework. These sessions highlighted the importance of improving data accessibility, embedding artificial intelligence in research and scaling digital decision-support systems. A dedicated fishbowl session helped clarify the structure and ambition of the artificial intelligence (AI) Hub, while a technical spotlight was given to a multilingual AI-powered agricultural large language model (AgriLLM) . Strategic site visits to the Technology Innovation Institute (TII), ATRC, Aspire and the Quantum Lab provided valuable exposure to cutting-edge innovations and opened new avenues for collaboration. A significant highlight was the introduction of a new UAE-based partner, including confirmation of major financial commitments: USD 7.5 million to the CGIAR Trust Fund and USD 20 million designated for DTA over 3 years, including USD 3.3 million earmarked for the AI Hub’s operationalization in Abu Dhabi. The workshop concluded with a clear roadmap and several key decisions: Revisiting and refining DTA’s theory of change; Onboarding additional CGIAR centers; and Establishing a program management community of practice (COP) to strengthen coordination and knowledge sharing. The workshop marked a critical milestone in setting a unified direction for CGIAR’s digital transformation, reinforcing a shared commitment to innovation, collaboration and long-term impact.